Mitigation measures of electromagnetic field exposure in the vicinity of high frequency welders - Bartłomiej Zubrzak; Paweł Bieńkowski; Pawel Cała (Nofer Institute of Occupational Medicine, 2017)
Background: Presented information about the welding process and equipment, focusing on the emission of electromagnetic field (EMF) with levels significant in terms of the labor safety regulations in force in Poland - the ordinances of the Minister of Family, Labour and Social Policy that came into force on June 27, 2016 and June 29, 2016 - emerged due to harmonization with European Union directive 2013/35/EU of 26 June 2013 of the European Parliament and the Council. They presented methods of determination of the EMF distribution in the welding machine surroundings and analyzed the background knowledge from the available literature. Material and Methods: The subject of the analysis included popular high frequency welders widely used in the industry. Electromagnetic field measurements were performed in the welder operating place (in situ) during machine normal operations, using measurement methods accordant with labor safety regulations in force in Poland and according to the same guidelines, the EMF distributions and parameters having been described. Results: They presented various scenarios of particular, real examples of excessive exposure to EMF in the dielectric welder surroundings and showed solutions, ranging from simple and costless and ending on dedicated electromagnetic shielding systems, which allowed to reduce EMF exposure in some cases of more than 80% (protection zone ranges) or eliminate dangerous zone presence. Conclusions: It has shown that in the dielectric welders surrounding, significant EMF strength levels may be the result of errors or omissions which often occur during development, installation, operation or modification of welding machines. It has allowed to present the measures that may significantly reduce the exposure to EMF of workers in the welder surroundings. The role of accredited laboratories in helping in such cases was underlined. Med Pr 2017;68(6):693-703